PERSEPSI MASYARAKAT TERHADAP ORGANISASI KEMASYARAKATAN PAC PEMUDA PANCASILA KECAMATAN LIMAPULUH KOTA PEKANBARU - Novrianto "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Problems of gangsterism which do Pemuda Pancasila is a problem that cannot be ignored, because a lot of thuggery Pemuda Pancasila taking repressivemeasures against the people, resulting Pemuda Pancasila get a bad perceptionamong the public. They say that the Pemuda Pancasila as Community Organisationsthugs. The purpose of this study was to determine the role of the Pancasila Youth inthe community, as well as actions undertaken Pancasila Youth thuggery, to identifyand analyze public perceptions of the youth public organizations in the District FiftyPancasila. The research method was use traditional quantitative methods. Datacollected by interview, observation, and documentation. Subjects in this study wereCommunity leaders, NGOs, as well as the District Fifty community. While the objectof this research is the public perception of community organization PemudaPancasila PAC District of Fifty. The results in this study show that (1). Publicperception of the organization Pemuda Pancasila is very bad, because people assumethat Pemuda Pancasila often repressive action (racketeering) in District Fifty. (2).There are many other activities that are carried out are thuggery such as PemudaPancasila, the collection of money cleanliness, collecting protection money, theseizure of the parking area, and competition for land development projects (assecurity) that is carried out by the government or private parties in the District ofFifty.Keywords: Organization, Percepcy, Society, and Gangsterims